2022
DOI: 10.1109/access.2022.3209665
|View full text |Cite
|
Sign up to set email alerts
|

Singe Image Dehazing With Unsharp Masking and Color Gamut Expansion

Abstract: Image dehazing is a fundamental problem in computer vision and has hitherto engendered prodigious amounts of studies. Recently, with the well-recognized success of deep learning techniques, this field has been dominated by deep dehazing models. However, deep learning is not always a panacea, especially for the practicalities of image dehazing, because high computational complexity, expensive maintenance costs, and high carbon emission are three noticeable problems. Computational efficiency is, therefore, a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…In [36], we demonstrated that the base algorithm achieves performance comparable to data-driven methods, such as those proposed by Cai et al [6] and Ren et al [22], while exhibiting significantly lower computational costs. However, real-time processing requirements through software implementation remain challenging.…”
Section: Base Algorithmmentioning
confidence: 70%
See 4 more Smart Citations
“…In [36], we demonstrated that the base algorithm achieves performance comparable to data-driven methods, such as those proposed by Cai et al [6] and Ren et al [22], while exhibiting significantly lower computational costs. However, real-time processing requirements through software implementation remain challenging.…”
Section: Base Algorithmmentioning
confidence: 70%
“…As data-driven methods are not yet ready for widespread deployment, this paper presents an alternative for real-time high-quality single-image dehazing: a symmetric MPSoC-based solution that balances the trade-off between dehazing performance and computational complexity. Building upon our previous work of linear-time single-image dehazing [36], the proposed algorithm incorporates the following features (as illustrated in Figure 1):…”
Section: Proposed Algorithmmentioning
confidence: 99%
See 3 more Smart Citations